Evaluation of Antibacterial Activity of Ethanolic Extracts for Three Local Plants - Al-Ameri, Kudair A. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
There is an increasing interest in the use of plant extracts as therapeutic agents, particularly their capacity to inhibit the growth of pathogenic microorganisms. In this study antibacterial effect of Malva sylvestris, Anastatica hierochuntica and Vitis vinifera leaves extracts were evaluated against Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Staphylococcus aureus and Proteus mirabilis. The in vitro antibacterial activity was performed using agar well diffusion method and the minimum inhibitory concentration (MIC) was determined by microtitration technique. The result indicated that the extract of V. vinifera leaves inhibited with the growth of gram-positive bacteria, as well as gram-negative bacteria while the extract of A. hierochuntica showed inhibitory activity against B. subtilis and S. aureus. Finally the extract of M. sylvestris showed inhibitory activity against E. coli, P. aeruginosa, S. aureus and P. mirabilis. Phytochemical studies showed that the active component in ethanolic extract of these plants have amino acid, glycoside, phenol, tannins and alkaloids.